Human Defensin-5 Blocks Ethanol and Colitis-Induced Dysbiosis, Tight Junction Disruption and Inflammation in Mouse Intestine. Issue 1 (December 2018) - Shukla, Pradeep; Meena, Avtar; Rao, Vaishnavi; Rao, Roshan; Balazs, Louisa; Rao, RadhaKrishna
Abstract Alcohol consumption has been shown to cause dysbiosis, but the mechanism involved in it is unknown. Recurrent colitis is known to induce expression of α-defensins in the colon, but the effect of alcohol consumption on it is not known. We investigated the effect of ethanol on α-defensin expression in the small intestine and colitis-induced expression in colon in mice. Furthermore, we evaluated the effect of human defensin-5 (HD5) on ethanol and colitis-induced gut barrier dysfunction and mucosal damage. Recurrent colitis was induced by feeding dextran sulfate sodium (DSS), 3 cycles of 5-days each with 15 days intervals, followed by 30-days remission. Ethanol was fed during the intervals and recovery in a liquid diet with or without HD5. Expression of α-defensins, tight junction (TJ) integrity and cytokine/chemokine expression were analyzed. Chronic ethanol feeding reduced α-defensin expression in the small intestine and colitis-induced defensin expression in the colon. HD5 attenuated the growth of enterotoxigenicBacteriodes fragilis andE. coli, but had no effect on non-toxigenicBacteriodes fragilis or probiotics, theLactobacilli . Ethanol and colitis elevatedEnterobacteriaceae, Firmicutes andFirmicutes toBacteriodetes ratio in colonic mucosa. HD5 feeding attenuated ethanol and colitis-induced dysbiosis, disruption of intestinal epithelial TJ, mucosal inflammation, expression of pro-inflammatory cytokines and chemokines in the small intestine and colon, and endotoxemia. These results demonstrate that ethanol suppresses intestinal α-defensin expression, leading to dysbiosis, barrier dysfunction, inflammation and endotoxemia. HD5 feeding attenuates intestinal injury caused by ethanol and colitis, indicating that defensin expression is a potential target for treatment of alcoholic tissue injury and colitis.